EVALUATION OF MOSUL INFLOW'S WASTEWATER QUALITY FOR IRRIGATION - Mohammed Abdullah; Abd Al-Kader Alhadede; Waheeda Al-badrani (Mesopotamia Journal of Agriculture)
Wastewater is industrial, and agricultural liquid wastes that contain biodegradable materials, as well as non-biodegradable materials and compounds., such as pesticides, and plastic. 80% of non-treatment wastewater globally is used to irrigate crops which leads to the accumulation of salts, compounds, and heavy metals in the soil and crops, which causes soil deterioration and problems in plant growth and may be transmitted to humans through the food chain. Nine sites were chosen for wastewater from Mosul inflow. Samples were collected monthly for each sites between March 2022 to February 2023. The results indicated that the concertation of lead, zinc, copper, nickel, and cobalt ranged (0.179 -1.533), (1.55 -2.69), (Nill-0.442), (0.201 -0.695) and (0.021-0.081) respectively, most sites exceeded the Iraqi standard for irrigation. The value of total solids (TDS), nitrates, phosphates, and sulfates ranged between (493 -845), (3.6-10.3), (2.3-6.2) and (162-350) respectively, all sites were within global and Iraqi standard limits for irrigation. Al-Danville inflow was the most polluted sites with lead and nickel because they collect industrial wastewater. Wastewater in all sites is considered very hard and can lead to deposits, blockage of pipes, and damage to irrigation systems. We recommend not using wastewater for irrigation in all sites Because it contains high concentrations of heavy elements and most of the characteristics exceeded the international and Iraqi standards of irrigation and this causes soil deterioration and pollution and poses health and environmental risks.